The importance of implementation maintenance manual for residential building / Norfatihah Mohd Rusli - Mohd Rusli, Norfatihah (Faculty of Architecture, Planning and Surveying, 2014)
Maintenance is one of the building management strategy aims to provide protection to the importance and usability of the buildings. Maintenance is also become an important approach in ensuring the building and its contents can be operate and function properly. However, based on previous studies, maintenance is always been neglected and not become the main activity in managing and protecting of the valuable and non replaceable asset. Therefore, the aim of this study is to establish the need of the implementation maintenance manual for residential building in order to assist the homeowner and tenant to correct identify any repairs or maintenance. To achieve this aim, three objectives have been delineated. The first objective is to study the need of implementation maintenance manual for residential building. The second objective is to investigate the problems regarding the maintenance faced by the homeowner or tenant and the third objective is to study the awareness on the importance of maintenance manual for residential building. Through the random sampling technique, the survey was conducted by distributing the questionnaire to 30 respondent for every case study in order to obtain the required data. So, the total numbers of respondents are 90 respondents. Then, the analysis of the data that was obtained was carried out by using the manual method with entering the information into the Microsoft Excel and generate a graph that relates for all parts of the questionnaire. The study concludes that the maintenance manual is very importance to the homeowners and tenants and it is need to be implement in the residential building in Malaysia.